JUVENILE ARTHRITIS DISEASE ACTIVITY SCORE IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS AND ITS ASSOCIATION WITH CLINICAL DISEASE ACTIVITY IN LAHORE: Juvenile Arthritis Disease - Nawaz, Zanera; Shahzad, Farhana; Aziz, Saba (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine Juvenile Arthritis Disease Activity Score in children with juvenile idiopathic arthritis and its association with disease activity. Study Design: Cross sectional analytical. Place and Duration of Study: The study was conducted in the department of Immunology & Serology, the Children Hospital and the Institute of Child Health Lahore, from Jun 2015 to Jun 2016. Material and Methods: All consecutive patients in a period of three months from Jun to Aug who fulfilled the inclusion criteria were enrolled from Out Patient Department and Medical Unit 1. Demographic profile including age and gender were recorded. Type of arthritis was assigned according to ILAR. The severity of the disease of patients was assessed by using the JADAS-27 score at the time of presentation. Statical analysis of data was done on SPSS version 17.0 for obtaining statistical results. Results: Out of 45 patients, 44% (n=20) were males and 56% (n=25) were females between the age of 3-17 years. polyarthritis was found in 51.1% (n=23) followed by oligoarthritis 37.7% (n=17) and systemic onset disease 11.1% (n=5). Morning stiffness (97.8%) and fever (86.7%) were the most common clinical presentations. All patients with systemic onset disease had fever (n=5) followed by skin rash, hepatosplenomegaly and lymphadenopathy. Creactive protein was positive in 30 (66.67%) patients. Erythrocyte sedimentation rate was raised in 41 (91.11%) patients. Rheumatoid factor (RF) positivity was observed in 12 (26.67%) cases. Anti-nuclear antibodies were found positive in 3 (6.66%) patients. Out of 45 patients 5 were in clinical remission, 11 were in minimal disease activity and 29 had severe clinical disease activity. Maximum 11 cases of severe disease activity lie between 30-40 JADAS-27 score each for CRP and ESR. Conclusion: There was significant association between Juvenile Arthritis Disease Activity Score and Clinical Disease Activity. CRP and ESR were proved to be good inflammatory markers in JIA.